TINJAUAN HUKUM TERHADAP PERUSAHAAN ALIH DAYA YANG MEMBERDAYAKAN TENAGA KERJA WAKTU TERTENTU DI KABUPATEN DELI SERDANG (STUDI KASUS PADA PT DIPTA ATHIYASA INDONESIA) - Agies Kharimantara Nakamura; Jaminuddin Marbun; Mhd. Taufiqurrahman (JURNAL PROINTEGRITA, 2021)
Many companies have changed their management structure to be more effective and efficient, one of which is by outsourcing work to other parties or employing workers with a fixed-time work agreement (PKWT) system. The problem in PKWT is that there is a violation in the application of the Agreement system in the form of deviations from the implementation of the rules for the Fixed Time Work Agreement (PKWT), which isnt in accordance Law Number 13 of 2003 concerning Manpower. The method used in this research is descriptive analysis research. The data used are secondary data. Data analysis used qualitative juridical analysis. The results showed that: 1) In the outsourcing practice by PT Dipta Athiyasa Indonesia, outsourcing contracts were not clearly classified as to the nature and type of work carried out; 2) PT Dipta Athiyasa Indonesia empowerment of workers through contract extension and give priority to workers who have worked before to be rehired; 3) Constraints faced in implementing a fixed-time work agreement (PKWT) are obstacles related to existing regulations, related to agreements and supervision. The solution is that the government should immediately make improvements to the arrangements for workers / laborers on a Fixed Time Work Agreement (PKWT), so that workers / laborers get better legal protection.